Hubungan Faktor Individu dengan Kelelahan Kerja Pada Karyawan di PT Adhi Persada Gedung Bekasi Tahun 2018 - Nela Agustin; Sariah Sariah (Jurnal Persada Husada Indonesia, 2018)
Work fatigue is part of a general problem often found in the workforce. The aim of this study was to find out the relationship between individual factors and work fatigue in employees of PT Adhi Persada Gedung Bekasi in 2018. Work fatigue happened due to work fatigue cause factors as individual factors. This study appluied quantitative approach with cross sectional study design. Population made up of 161 employees of PT Adhi Persada Gedung Bekasi in 2018 with 62 employees samples. Accidental technique was used in the sample understanding. Questionaires were used as the instruments. Data analysis was performed univariate and bivariate (applied alternative Fisher test with α=0,05). Based on study results, it is known that all employees experience fatigue, namely 27 employees (43.5%) experienced mild work fatigue and 35 employees (56.5%) experienced heavy work fatigue. Study results also showed the presence of 4 variables possessing significant relationship, i.e. age with work fatigue (P=0,000), work period with work fatigue (P=0,007), marital status with work fatigue (P=0,000) and work type with work fatigue (P=0,019). Study result concluded the existence of the relationship between individual factors and work fatigue. It is recommended for employees to use the rest time as optimal as possible to reduce work fatigue. Recommendation for the company to pay more attention to the conditions of the employees.